Functional components of public expenditure, fiscal consolidations and the economic activity - Castro, Vítor (2016)
This paper analyses how the functional components of public expenditure and spending-driven consolidations affect the economic growth, unemployment and income inequality. A dynamic panel data LSDVC estimator is employed over a sample of 15 European Union countries during the period 1990-2012. The empirical results show that real GDP growth decreases when fiscal austerity measures are implemented, especially if they are spending-driven. Cuts in public expenditure undermine economic growth, namely if they slash spending on public order, recreation and education. Spending cuts on education, in particular, affect the investment in human capital, harming not only growth but also economic, social and human development. The unemployment rate also proved to be significantly boosted when austerity measures restrict spending on education, while income inequality rises when social protection expenditures are cut.